anonymous
  • anonymous
check my work
Mathematics
chestercat
  • chestercat
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
Q:Find \[\iint_\limits S (\vec \nabla \times \vec F).\hat n \space ds\] where \[\vec F=(x-z)\hat i+(x^3+yz)\hat j+3xy^2 \hat k\] and S is the surface of the cone \[z=a-\sqrt{x^2+y^2}\] above the xy plane Now \[\vec \nabla \times \vec F=\left|\begin{matrix}\hat i & \hat j & \hat k \\ \frac{\partial}{\partial x} & \frac{\partial}{\partial y} & \frac{\partial}{\partial z}\\x-z & x^3+yz & 3xy^2\end{matrix}\right|\]\[\vec \nabla \times \vec F=\hat i(6xy-y)-\hat j(3y^2+1)+3x^2 \hat k=y(6x-1)\hat i-(3y^2+1)\hat j+3x^2 \hat k\] We can re-write our equation for cone as \[\sqrt{x^2+y^2}+z=a\] Which is of the form \[\phi(x,y,z)=c\] Equation of a level surface, where phi is a scalar function of x,y,z and c is a constant In this case, a vector normal to the surface is given by \[\vec n=\vec \nabla \phi=(\hat i \frac{\partial \phi}{\partial x}+\hat j \frac{\partial \phi}{\partial y}+\hat k \frac{\partial \phi}{\partial z})\]\[\vec n=\frac{1}{2\sqrt{x^2+y^2}}.2x \hat i+\frac{1}{2\sqrt{x^2+y^2}}.2y \hat j+\hat k=\frac{x \hat i}{\sqrt{x^2+y^2}}+\frac{y \hat j}{\sqrt{x^2+y^2}}+\hat k\] \[|\vec n|=\sqrt{\frac{x^2}{x^2+y^2}+\frac{y^2}{x^2+y^2}+1^2}=\sqrt{\frac{x^2+y^2}{x^2+y^2}+1}=\sqrt{1+1}=\sqrt{2}\] \[\hat n=\frac{\vec n}{|\vec n|}=\frac{1}{\sqrt{2}}(\frac{x \hat i}{\sqrt{x^2+y^2}}+\frac{y \hat j}{\sqrt{x^2+y^2}}+\hat k)\] When \[z=0\] We have \[x^2+y^2=a^2\] This is the projection of the cone in xy-plane (circle of radius a in the xy-plane), |dw:1443798608113:dw| Thus we convert our surface integral... \[\iint_\limits S (\vec \nabla \times \vec F). \hat n \space ds=\iint_\limits {R}(\vec \nabla \times \vec F). \hat n \space \frac{dxdy}{\hat n.\hat k}\] where R is the region covered by circle of radius a \[\therefore \hat n=\frac{1}{\sqrt{2}}(\frac{x}{a}\hat i+\frac{y}{a}\hat j+\hat k)=\frac{1}{\sqrt{2}a}(x \hat i+y \hat j+a \hat k)\] Now \[(\vec \nabla \times \vec F).\hat n=\frac{1}{\sqrt{2}a}(y(6x^2-x)-(3y^3+y)+3ax^2)\] Also \[\hat n . \hat k=\frac{1}{\sqrt{2}} \implies \frac{1}{\hat n . \hat k}=\sqrt{2}\]\[(\vec \nabla \times \vec F).\hat n \frac{1}{\hat n . \hat k}=\frac{1}{a}(y(6x^2-x)-(3y^3+y)+3ax^2)\]\[\frac{(\vec \nabla \times \vec F).\hat n}{\hat n . \hat k}=\frac{1}{a}(y(6x^2-x-1)-3y^3+3ax^2)\] Thus our surface integral is \[\therefore \frac{1}{a}\iint_\limits R [y(6x^2-x-1)-3y^3+3ax^3]dydx\] Using a short hand notation for the left side \[\iint_\limits R =\frac{1}{a} \int\limits_{-a}^{a}[\int\limits_{-\sqrt{a^2-x^2}}^{\sqrt{a^2-x^2}}((6x^2-x-1)y-3y^3+3ax^2)dy]dx\] \[\iint_\limits R=\frac{1}{a}\int\limits_{-a}^{a}[(6x^2-x-1)\int\limits_{-\sqrt{a^2-x^2}}^{\sqrt{a^2-x^2}}ydy-3\int\limits_{-\sqrt{a^2-x^2}}^{\sqrt{a^2-x^2}}y^3dy+3ax^2\int\limits_{-\sqrt{a^2-x^2}}^{\sqrt{a^2-x^2}}dy]dx\] \[\iint_\limits R=\frac{1}{a}\int\limits_{-a}^{a}[0+0+6ax^2\int\limits_{0}^{\sqrt{a^2-x^2}}dy]dx=\frac{1}{a}\int\limits_{-a}^{a}6ax^2\sqrt{a^2-x^2}dx\] \[\iint_{R}=6\int\limits_{-a}^{a}x^2{\sqrt{a^2-x^2}}dx=12\int\limits_{0}^{a}x^2\sqrt{a^2-x^2}dx\]\[x=a\sin(\theta)\]\[\therefore dx=a\cos(\theta)d \theta\] The limits transform as \[0 \rightarrow 0 \space , \space a \rightarrow \frac{\pi}{2}\] \[\iint_\limits R=12 \int\limits_{0}^{\frac{\pi}{2}}a^2\sin^2(\theta).a^2\cos^2(\theta)d \theta=12a^4\int\limits_{0}^{\frac{\pi}{2}}(\sin(\theta)\cos(\theta))^2d \theta\] \[\iint_\limits R=3a^4 \int\limits_{0}^{\frac{\pi}{2}}(2\sin(\theta)\cos(\theta))^2d \theta=3a^4\int\limits_{0}^{\frac{\pi}{2}}\sin^2(2 \theta)d \theta\]\[\iint_\limits R=\frac{3a^4}{2}\int\limits_{0}^{\frac{\pi}{2}}(1-\cos(4\theta))d \theta=\frac{3a^4}{2}[\theta-\frac{\sin(4 \theta)}{4}]_{0}^{\frac{\pi}{2}}\]\[\iint_\limits R=\frac{3a^4}{2}[\frac{\pi}{2}-\frac{\sin(2\pi)}{4}-(0+\frac{\sin(0)}{4})]=\frac{3a^4}{2}(\frac{\pi}{2}+0+0+0)=\frac{3 \pi a^4}{4}\]
Jhannybean
  • Jhannybean
You must've got an integration error somewhere right? :P
anonymous
  • anonymous
Yikes!! Don't say such scary stuff, I miss the questions in school! Questions like these in college take a lot of time for a single question :(

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Michele_Laino
  • Michele_Laino
I have computed the integral in a different way, and I got the same result
anonymous
  • anonymous
sweet :D

Looking for something else?

Not the answer you are looking for? Search for more explanations.